European Society of Gynecological Oncology Statement on Fibroid and Uterine Morcellation. Issue 1 (1st January 2016) - Halaska, Michael J.; Haidopoulos, Dimitrios; Guyon, Frédéric; Morice, Philippe; Zapardiel, Ignacio; Kesic, Vesna
Abstract : Abstract: Recently, there has been an intense discussion about the issue of fibroid and uterine morcellation in relation to the risk of unrecognized uterine sarcoma spread. Morcellation can negatively influence the prognosis of patients, and transecting the specimen into pieces prevents the pathologist from performing proper disease staging. Many societies have published their statements regarding this issue. The European Society for Gynecological Oncology has established a working group of clinicians involved in diagnostics and treatment of oncogynecological patients to provide a statement from the oncological point of view. Leiomyosarcomas and undifferentiated endometrial sarcomas have generally dismal prognosis, whereas low-grade endometrial stromal sarcomas and adenosarcomas have variable prognosis based on their stage. A focus on the detection of patients at risk of having a sarcoma should be mandatory before every surgery where morcellation is planned by evaluation of risk factors (African American descent, previous pelvic irradiation, use of tamoxifen, rapid lesion growth particularly in postmenopausal patients) and exclusion of patients with any suspicious ultrasonographic signs. Preoperative endometrial biopsy should be mandatory, although the sensitivity to detect sarcomas is low. An indication for myomectomy should be used only in patients with pregnancy plans; otherwise en bloc hysterectomy is preferred in both symptomatic and postmenopausal patients. Eliminating the technique of morcellation could lead to an increased morbidity in low-risk patients; therefore, after thorough preoperative evaluation and discussion with patients, morcellation still has its place in the armamentarium of gynecologic surgery.